Water and Sanitation as a Wicked Governance Problem in Brazil: An Institutional Approach - Carvalho, Denise Moraes; van Tulder, Rob (Frontiers in Water, 2022)
The world is facing a large number of interrelated crises that have seriously increased the level of uncertainty and ambiguity in many areas. In 2018, the UN anticipated that the world was careering towards a global water crisis with a 40% shortfall in freshwater resources by 2030 coupled with a rising population. This nascent crisis represents a ‘connected challenge’ for countries: it contains a multitude of causes and consequences, a multitude of actors and interests for which no ‘one-size-fits-all’ solutions are available. The adequate approach to this type of complex – or ‘wicked’- problems is not to search for technological solutions only, but to consider new forms of governance that make use of complementary institutional logics. Effective governance depends on the extent of alignment with the complexity and the root causes of the issues. This paper applies wicked problem theory to identify the root institutional and governance causes of uncertainty in a developing country like Brazil, which provides insights to (also) identify approaches that could navigate change in less uncertain and ambiguous directions. We distinguish three types of relevant institutional constraints: logics, complementarities, and voids. Based on semi-structured interviews with representatives from Brazil’s water and sanitation sector, we delineate institutional constraints precipitated by the plurality of the governance system. We argue why a tripartite partnership approach – as for instance pioneered by Dutch international water projects in the global South - presents a way out of the wicked water and sanitation problems in Brazil.